anonymous
  • anonymous
Solve by substitution method 2x-5y=-1 x -3y=-3 I really want step by step please.
Mathematics
jamiebookeater
  • jamiebookeater
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this
and thousands of other questions

anonymous
  • anonymous
2x-5y=-1 x-3y=-3 x-3y=-3 we solve for x. Since it's easier. we do this by adding -3y to both sides X=-3+3y then we plug in (-3+3y) in for x in the equation 2x-5y+=-1 2(-3+3y)-5y=-1 We distributed the 2(-3+3y) it equals -6y+6y in which the cancel out each other. we get -5y=-1 Divide both sides by -5 \[y=\frac{1}{5}\]
anonymous
  • anonymous
thanks I still dont understand
anonymous
  • anonymous
oops sorry i made a mistake. i'll correct it right now.

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
2x-5y=-1 x-3y=-3 x-3y=-3 we solve for x. Since it's easier. we do this by adding -3y to both sides X=-3+3y then we plug in (-3+3y) in for x in the equation 2x-5y+=-1 2(-3+3y)-5y=-1 We distributed the 2(-3+3y) it equals -6+6y -6+6y-5y=-1 6y-6y =y -6+y=-1 subtract negative -6 from both sides. -1--6=5 y=5

Looking for something else?

Not the answer you are looking for? Search for more explanations.